Estrategias pedagógicas activas en el proceso de aprendizaje de los estudiantes con necesidades educativas especiales del primer año de bachillerato de la unidad educativa Quintiliano Sánchez Rendón del cantón Buena Fe, periodo 2021-2022 - Vélez Vélez, María Alexandra (2021)
The Strategies Active pedagogical are procedures that precisely guide the path to effective learning, relying on key components such as experience, reflection, conceptualization and metacognition, where the student is the center and axis of the teaching process. This research was consolidated in the Unit Quintiliano Sánchez Rendón Educational, which is located in the city of Buena Fe, Los Ríos Province; The development of this research required as a sample the group of teachers who teach classes in the first year of high school, giving a total of 20 servers, to whom the survey instrument was applied, relevant for the diagnosis of the problem. The research was of a quantitative approach, descriptive, purposeful and documentary, favoring the understanding of the variables, through the appropriate foundation, which guided towards the design of an improvement proposal. Its objective is to establish Strategies Active pedagogical that optimize the learning process of students with Needs Educational Special in the first year of Baccalaureate at the Unit Quintiliano Sánchez Rendón Educational. Among its specific objectives, it seeks to carry out a pedagogical diagnosis, determine the theoretical foundations, design a teacher training plan and assess the effectiveness of Strategies Active pedagogical. The research answered the questions posed around the identified problem, becoming a highly valuable resource for the projection of motivational pedagogical activities, the design of efficient planning and the continuous evaluation of educational management within the framework of inclusive education.